A abordagem da relação transtorno mental e trabalho pela justiça do trabalho - Souza, Mirella Darc de Melo Cahú Arcoverde de (2023)
This dissertation aims to analyze how professionals who are involved in labor court actions deal with the relationship between mental disorders and work. Psychodynamics of labor is the theoretical basis used to analyze this relationship. The research was structured as follows: first, a review of the relationship between mental disorder and work from the point of view of the psychodynamics of labor; then, the treatment of the theme given by professionals who work in labor court actions in four clippings of procedural documents (initial application, defense, expertise and sentence) and, finally, the analysis of five concrete cases from each of the geographic regions of Brazil. The research hypothesis was confirmed in the sense that the lawsuits have requested from the subjects involved in the process (judges, lawyers, experts) technical support, not always sufficient, in order to give attention to the singularities of the relationship between mental disorder and work, since this theme is not ordinary for most of the subjects involved. Furthermore, judges have been nominating experts with different backgrounds, such as general physicians, occupational physicians, psychiatrists, or psychologists, who have taken on the task of producing an expert report that will serve as support for the decision. That the reports normally produced are based on theoretical criteria freely chosen by the professional responsible for the task, without any prior indication in the legal regulations about the methodology of approach, capable of demonstrating to the parties of the process which elements can be considered as definers of the disease/work relationship. We propose as an action that there should be theoretical improvement on the theme, with an interdisciplinary exchange involving mental health and work, so that individual aspects of the ill worker can be analyzed, but also the collective experience undergone, in order to effectively guarantee justice in the lawsuits that are being processed in the labor courts.